Jasmin: Barber, Poet, Philanthropist - Smiles, Samuel, 1812-1904 (Salt Lake City, UT : Project Gutenberg, 1997)
"Jasmin: Barber, Poet, Philanthropist" by Samuel Smiles is a biography written in the late 19th century that chronicles the life of Jacques Jasmin, a notable figure from the South of France. It explores his journey from a life of poverty in Agen to becoming a celebrated poet and philanthropist, emphasizing his contributions to the Gascon dialect and his charitable works. The opening of the biography introduces readers to Jasmin's early life, detailing his humble beginnings as the son of a struggling tailor and laundress in Agen. It paints a vivid picture of his childhood experiences, from the challenges of poverty to moments of joy shared with friends. The narrative highlights Jasmin's early encounters with poetry, encouraged by his father's rhymes and his grandfather's rich storytelling. As the story progresses, readers witness his struggles with education, his eventual apprenticeship as a barber, and the awakening of his poetic ambitions, which become pivotal in his journey toward recognition and philanthropy. (This is an automatically generated summary.)
Release date is 1997-03-01
Produced by Eric Hutton, and David Widger
Keywords: Jasmin, 1798-1864; Poets, French -- Biography